The Use of Rosetta Stone in Enhancing Junior High School Students’ Pronunciation - Rani Syahda Hanifa; Dian Rahma Santoso (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This study aims to improve the quality of students' pronunciation with a sample of grade 7 students at SMP Muhammadiyah 8 Tanggulangin. The importance of this research is carried out so that students get effective learning regarding pronunciation using digital media which in this era is very close to them. Using the CALL theoretical framework and the Action Research method carried out inside and outside the classroom, the researcher conducted 2 cycles to achieve success in research results. The result is that by learning pronunciation using the Rosetta Stone application, students have a significant increase and reach 100% of the minimum grades at school before this treatment was held, only 20% of students succeeded in exceeding the school's minimum grades. Through interviews about how students' perspectives regarding the application were also found in cycle 2 as much as 0% complaint.